Cell surface protein partially restores morphology, adhesiveness, and contact inhibition of movement to transformed fibroblasts. - Yamada, K M (1976)
We have isolated the major cell surface glycoprotein of chick embryo fibroblasts, CSP, and added it to a variety of transformed cells in vitro. The transformed cells become more elongated, often more flattened, and show increased adhesion to the substratum. Several transformed cell lines also align in striking parallel arrays. This alignment is characterized by a decrease in the amount of nuclear overlapping, probably indicating restoration of contact inhibition of movement. The morphological changes are antagonized by antibody to CSP. These effects of CSP are not associated with an elevation of cellular 3':5'-cyclic AMP. Moreover, the morphological reversion is not accompanied by an alteration in growth properties. Our results are consistent with a role for CSP in cell adhesion and morphology but not in growth control.